Ultrastructural Studies on the Isthmus and Uterus of Oviduct in Emu (Dromaius novaehollandiae) - Naik, Raghu (Indian Journal of Veterinary Anatomy, 2021)
The ultrastructure of isthmus and uterus was studied in emu birds. The mucosa of isthmus contained large flat and broad mucosal folds having pseudostratified etithelium columnar ciliated. Clusters of mitochondria were observed around the roots of the cilia. The apical material was bulged into the lumen of the isthmus and gave bleb appearance. The secretory acini were lined with pyramidal cells containing electron dense secretory granules.The mucosa of uterus contained leaf like longitudinal folds, which were compact and tortuous and separated by deep narrow clefts. It was lined by ciliated cells with several openings of the tubular glands opening on to the surface. The surface epithelium was pseudostratified columnar type. The ciliated cells presented well developed cilia intermingled with microvillion their apical surfaces. The tubular glands were lined by pyramidal shaped cells with numerous microvilli on their luminal surface.